Isolation and Identification of Protease Enzyme Producing Bacteria from Fermentation of Gonad Sea Urchin (Echinothrix calamaris) - Siani La Jamaludin; Johanis Fritzgal Rehena; Cecilia Anna Seumahu; Dominggus Rumahlatu (Marine Science Department Diponegoro University, 2018)
Bekasang of gonad sea urchin is one of the traditional fermentation products which generally involves microorganism spontaneous fermentation. Fermented paste products have a long shelf life and are processed quite easily using protease enzymes. Good exploration of producing protease from bakasang is needed to obtain the protease enzyme-producing microorganism with different characters. The method used in this research is screening with clear zone, measuring the activity of crude extract of protease enzyme characterization of bacteria through gram staining. Identification of potential microorganisms through 16S rRNA sequence. The results showed that there were eight isolates of protease enzyme-producing bacteria (G1, G2, G3, G4, G5, G6, G7, and G8) indicated by clear zones around single-colonic bacterial streaks. Only five bacterial isolates (G1, G4, G6, G7, and G8) were tested for the enzyme activity. These isolates have characteristics of positive gram bacteria. The interpretation of the results of molecular analysis using PCR and BLASTN sequences of 16S rRNA gene from five bacterial isolates, showed the identity of bacteria as: G1 was Staphylococcus piscifermentans strain CIP103958 with 99% similarity; Isolate G4 was Staphylococcus saprophyticus strain ATCC 15305 with 99% similarity; Isolate G6 was Staphylococcus condimenti F-2 strain with 99% similarity; Isolate G7 was Bacillus amyloliquefaciens subsp. plantarum strain FZB42 with 99% similarity; And G8 isolates was Lactobacillus plantarum strain JCM 1149 with 99% similarity.